Online Newspaper Coverage of the “Bring Back Our Girls” Campaign in Nigeria - Jibril, A. (University of Ghana, 2015)
In this study, attempt has been made to determine the coverage of Bring Back Our Girls (BBOG) campaign in Nigeria by online newspapers. Seventy-one editions of Daily Trust, the Punch, Sahara Reporters and Vanguard newspapers from April 2014-October 2014 were content analysed. The study examined how much coverage BBOG campaigns received in the sampled online newspapers, the nature of reporting BBOG campaigns and the dominant sources of stories and themes in the framing of stories on the campaign in the newspapers studied. Making use of qualitative and quantitative content analysis and secondary sources of data, the study found that the newspapers provided mostly favourable coverage of the campaign with a total of 59 (83.1%) out of 71 total stories. The study also found that the campaigners and their sympathisers were the dominant sources of stories during the study period. The study adopted framing theory as a theoretical basis of the study. The study concluded that the newspapers made concerted efforts to cover the campaign positively, unlike what usually obtains in Western media framing of social movements where status quo biases are often maintained. The study also found that the newspapers focused more on straight news than other story types in reporting the campaigns.
Thesis (MA) - University of Ghana, 2015
Keywords: Newspaper Coverage; Bring Back Our Girls; Campaign in Nigeria